Factor that build youth’s intention to do adventure tourism in kelantan - Muhammad Ariff Syakirl Hairol; Muhammad Ashrof Ridhuan; Muhammad Azam Ezaidi Marzuki; Muhammad Fairul Daniel Izhar (2022)
The migration of individuals from one place to another outside their comfort zone for exploration or travel to remote, exotic, and sometimes violent regions is characterized as adventure tourism. Young travelers enjoy adventure tourism the most and much of the thrill in adventure tourism stems from allowing travelers to move outside of their comfort zone. The aim of the research is to determine the factors that build youth/s intention to do an adventure tourism in Kelantan. Therefore, it’s crucial to comprehend the factors build youth’s intention to do adventure tourism include place attraction, facilities and environmental education. In addition, to ensure the intention is guaranteed the person must carry out a research method which is the factors that build youth’s intention to do adventure tourism in Kelantan. Several qualities must be investigated, including purpose, precision, objectivity, and others. All of these aspects contribute to thorough research. This study is also conducted quantitatively. This method is crucial in determining what kind of observation should be used to obtain information on factors that build youth/s intention to do an adventure tourism in Kelantan. The goal of research methodology is to gather, process, and analyse data in a systematic and efficient manner in order to finish a study. Each research must have a purpose, objectivity, and a technique to ensure that the investigation yields the desired results or answers.